Cytotoxicity Activity and Phytochemical Screening of Cochlospermum tinctorium Perr Ex A. Rich Rhizome - Akpemi Audu Musa (Journal of Applied Pharmaceutical Science)
Cytotoxicity activity experiment was carried out on the polar fractions of Cochlospermum tinctorium using the brine shrimp lethality bioassay method. The LC50 values of the extracts were determined by linear regression analysis method. It was observed that the 80% acetone extract LC50 value was 240 ± 3 µg/ ml, which was more potent compared to n-butanol extract with LC50 value of 437 ± 8 µg/ ml. Phytochemical test performed on both extracts showed that they contained cardiac glycosides, saponins and carbohydrates, while only the 80% acetone extract contains anthraquinones, flavonoids and tannins. These secondary metabolites present in both extracts, may likely accounts for their cytotoxic activity.
Keywords: Brine shrimp lethality bioassay,cytotoxic,antitumor,Cochlospermum tinctorium,probit analysis,anticancer.